Coxiella burnetii and Leishmania mexicana residing within similar parasitophorous vacuoles elicit disparate host responses - Millar, Jess A.; Valdés, Raquel; Kacharia, Fenil R.; Landfear, Scott M.; Cambronne, Eric D.; Raghavan, Rahul (Frontiers in Microbiology, 2015)
Coxiella burnetii is a bacterium that thrives in an acidic parasitophorous vacuole (PV) derived from lysosomes. Leishmania mexicana, a eukaryote, has also independently evolved to live in a morphologically similar PV. As Coxiella and Leishmania are highly divergent organisms that cause different diseases, we reasoned that their respective infections would likely elicit distinct host responses despite producing phenotypically similar parasite-containing vacuoles. The objective of this study was to investigate, at the molecular level, the macrophage response to each pathogen. Infection of THP-1 (human monocyte/macrophage) cells with Coxiella and Leishmania elicited disparate host responses. At 5 days post-infection, when compared to uninfected cells, 1057 genes were differentially expressed (746 genes up- and 311 genes down-regulated) in C. burnetii infected cells, whereas 698 genes (534 genes up- and 164 genes down-regulated) were differentially expressed in L. mexicana infected cells. Interestingly, of the 1755 differentially expressed genes identified in this study, only 126 genes ( 7%) are common to both infections. We also discovered that 1090 genes produced mRNA isoforms at significantly different levels under the two infection conditions, suggesting that alternate proteins encoded by the same gene might have important roles in host response to each infection. Additionally, we detected 257 micro RNAs (miRNAs) that were expressed in THP-1 cells and identified miRNAs that were specifically expressed during Coxiella or Leishmania infections. Collectively, this study identified host mRNAs and miRNAs that were influenced by Coxiella and/or Leishmania infections. Intriguingly, our data indicate that although their PVs are morphologically similar, Coxiella and Leishmania have evolved different strategies that perturb distinct host processes to create and thrive within their respective intracellular niches.